Relationship between the mother's characteristics and her performance of treatment programmes for her handicapped infant - T. H.A. Kolobe (AOSIS, 1983)
Maternal characteristics of 25 mothers measured by questionnaire scales and their performance of their infants' physiotherapy treatment activities were correlated to determine the nature of this relationship. The results showed that mothers with positive attitudes, internal locus of control and middle socioeconomic status tend to perform their infants' treatment activities better than do mothers with negative attitudes, external locus of control and low socioeconomic status. The results also add support to the idea that if professionals involved in early intervention programmes are to help the child in a meaningful and effective way, they should be aware not only of the child's developmental status, but also of the mother's mental or emotional status and be prepared to provide help in the lacking areas. The findings also indicate that the effectiveness of early intervention programmes will not only depend on the type of therapeutic techniques utilized but on the mother. The mother's attitude was the main contributor to how well she performed her infant's treatment activities.